Acute hyponatraemia in children admitted to hospital: retrospective analysis of factors contributing to its development and resolution. Issue 7289 (31st March 2001) - Halberthal, Michael; Halperin, Mitchell L; Bohn, Desmond
Abstract : Do not infuse a hypotonic solution if the plasma sodium concentration is less than 138 mmoVl